Corporate Tax Havens and Transparency. (2nd November 2017) - Bennedsen, Morten; Zeume, Stefan
Abstract: We investigate shareholders' reactions to the increased transparency of corporate tax haven activities in a hand-collected subsidiary data set covering 17, 331 publicly listed firms in 52 countries. An increase in transparency through the staggered signing of bilateral tax information exchange agreements (TIEAs) between home countries and tax havens is associated with a 2.5% increase in the value of affected firms. The results are stronger for firms with more complex tax haven structures and weakly governed firms. Furthermore, firms that respond to TIEAs by haven hopping (i.e., they move subsidiaries from affected to nonaffected tax havens) do not experience an increase in firm value. These results are consistent with tax havens being used for expropriation activities that extend beyond pure tax-saving activities. Received March 4, 2017; editorial decision October 5, 2017 by Editor Andrew Karolyi. Authors have furnished an Internet Appendix, which is available on the Oxford University PressWeb site next to the link to the final published paper online.